Fitness Trainers’ Price Policy: Evidence from Poland - Marcin KOMANDA (Communications of International Proceedings, 2021)
The subject area of the fitness industry is becoming a popular research question in the field of management science. Nowadays, the predominant descriptions of this industry are mainly national, presenting the specificity of social, economic, institutional, and technological conditions for conducting business activity within sport and recreation (Valcarce-Torrente et al., 2021; Mohammadi et al., 2021; Ebada et al., 2021; Anderson et al. 2021). There are also attempts made to define trends shaping the development of the industry in global terms (Thompson, 2019) or in terms of a specific region, e.g., Europe (Batrakoulis, 2019). One of the basic problems discussed in the research results is the issue of service quality in the context of the cost intensity of the proposed offer as well as the customers’ willingness to incur the costs (Brown, 2015). The objective of this paper is therefore to determine a specific aspect of the price policy of fitness trainers towards their clients in Poland, namely giving discounts. For the purposes of achieving this objection, a survey questionnaire was used by means of which fitness trainers with registered businesses were questioned regarding the use of discounts for regular and new clients. This issue was also linked to the form of services provided. The main findings make it possible to state that there is a generally weak tendency among trainers to treat regular and new clients in the same way in terms of giving them discounts. However, in the case of one-on-one services, new clients are less likely to expect discounts.
Keywords: Fitness; Trainer; Price; Policy.